Phagocytic activity of peripheral blood monocytes under in vivo and in vitro hypoxia conditions in tolerant and susceptible to oxygen deficiency rats - D. Sh. Dzhalilova; A. M. Kosyreva; I. S. Tsvetkov; O. V. Makarova (Медицинская иммунология, 2023)
It is known that there are individual differences in resistance to hypoxia, which can determine the predisposition to the development and severity of various diseases, including infectious, inflammatory and tumor. There are no standardized methods for assessing resistance to hypoxia in experimental animals and humans without hypoxic exposure. The search for molecular-biological markers, identifying people with different resistance to oxygen deficiency under normoxic conditions or under moderate hypoxic exposure is undoubtedly efficient. It is possible that the assessment of the basic resistance to hypoxia can help to predict the development and severity of the course of diseases, the mechanisms of which are associated with oxygen deficiency. One of the methods to assess organism resistance to hypoxia without exposure in a decompression chamber or in highland conditions can be modeling hypoxia in vitro. The aim of the study was to characterize the phagocytic activity of peripheral blood monocytes in tolerant and susceptible to hypoxia Wistar rats under normoxic conditions, as well as after hypoxic exposure in vitro and in vivo. The resistance of rats to hypoxia was determined by the gasping time at an altitude of 11.500 m in a decompression chamber. A month after determining the resistance to hypoxia, one group of rats was placed in a decompression chamber at an altitude of 5,000 m for 1 hour to simulate the hypoxic state in vivo. Blood from the tail vein of the other group of rats was placed in 1% oxygen for 1 hour to simulate the hypoxic state in vitro. The phagocytic activity of peripheral blood monocytes was assessed by flow cytometry. It was demonstrated that phagocytic activity of monocytes did not differ in tolerant and susceptible to hypoxia rats under normoxic conditions. The phagocytic activity of monocytes after in vitro and in vivo hypoxic exposure was higher in tolerant to hypoxia animals in comparison to susceptible ones. An increase in the phagocytic activity of monocytes compared to normoxia conditions was observed only in tolerant rats under in vitro conditions of hypoxic exposure. The obtained results indicate that tolerant and susceptible to hypoxia organisms differ in the phagocytic activity of monocytes under conditions of oxygen deficiency, which can determine the course of inflammatory and tumor diseases. The data obtained will be the basis for further experimental investigations organism hypoxia resistance markers.